FARMERS’ MOTIVATION IN INTENSIVE CATTLE FARMING IN PANDAWAI SUB-DISTRICT EAST SUMBA DISTRICT - J. H. K., Marak; Inggriati, N. W. T.; Suarta, I G. (Jurnal Peternakan Tropika, 2021)
This study examined farmers’ motivation in performing intensive cattle farming and analyzed factors affecting their motivation. This study was conducted in Pandawai Sub-District, East Sumba District from October to November 2019. Stratified random sampling was performed to select 45 samples in Pandawai District. Descriptive qualitative analysis and spearman level correlation test were performed to analyze the data. The results showed that farmers’ motivation in farming cattle intensively was categorized intermediate. Some factors including formal education, non-formal education, knowledge and attitudes had strong and significant influence on their motivation, while the intensity of communication also affected farmers’ motivation. In addition, age, length of farming cattle, livestock ownership and family responsibilities did not significantly affected farmers’ motivation. From research it could suggest that the motivation of farmers in performing intensive cattle farming in Pandawai Sub-district, East Sumba Regency was in the intermediate category. Knowledge, attitudes, formal education, non-formal education, and intensity of communication were factors that had significant influence on farmers’ motivation. Suggested staffs of the Livestock Service Office are suggested to improve the assistance and counselling for breeders to increase farmers’ motivation in farming their cattle intensively. Farmers are expected to be more active in carrying out intensive cattle farming for greater productivity, income and welfare. Key words : Motiva tion , farmers, cattle, intensive